Methane formation from photoreduction of CO2 with water using TiO2 including Ni ingredient. (1st March 2015) - Kwak, Byeong Sub; Vignesh, K.; Park, No-Kuk; Ryu, Ho-Jung; Baek, Jeom-In; Kang, Misook
Graphical abstract: Photocatalytic CO2 reduction with H2 O to CH4 over TiO2 and Ni–TiO2 . Highlights: Ni-incorporated TiO2 was synthesized using a solvothermal method. The photocatalytic activity was measured by the reduction of CO2 to CH4 . 14 μmol/gcatal of CH4 was produced during 60 min using Ni–TiO2 (0.1 mol%). Abstract: Photocatalysis is one of the most potential methods to reduce CO2 into useful compounds. In this work, in order to improve the photo reduction of CO2, nickel ions were incorporated in TiO2 and used as photocatalyst. XRD and TEM results showed TiO2 anatase structure with a nanoparticle. The character of surface was measured using BET and zeta potential. The photochemical properties were confirmed by UV–visible and PL. The CO2 reduction was tested in a liquid photoreactor and the products were analyzed in a GC. The highest yield of methane was observed on Ni–TiO2 (0.1 mol%) than that of other catalysts.